Avaliação do potencial anticorrosivo de tiossemicarbazonas solubilizadas em microemulsão Evaluation of anticorrosive effectiveness of thiosemicarbazones solubilized in a microemulsion system - Elaine Cristina M. de Moura; Adna Dornelles N. Souza; Cátia Guaraciara F. T. Rossi; Djalma R. da Silva; Maria Aparecida M. Maciel; Aurea Echevarria; Myrtes S. S. Bellieny (Química Nova, 2013)
In this paper, thiosemicarbazones 4-N-cinnamoyl-thiosemicarbazone (CTSC), 4-N-(2'-methoxycinnamoyl)-thiosemicarbazone (MCTSC), and 4-N-(4'-hydroxy-3'-methoxybenzoyl)- thiosemicarbazone (HMBTSC) were solubilized in an oil-in-water (O/W) microemulsion system (ME_OCS), forming systems CTSC_ME_OCS, MCTSC_ME_OCS and HMBTSC_ME_OCS. The effectiveness of these systems in the process of inhibiting AISI 1020 carbon steel corrosion was evaluated in a saline solution (NaCl 0.5%), using a galvanostatic method. The tested thiosemicarbazones showed higher inhibitory effects (85.7% for CTSC_ME_OCS, 84.0% for MCTSC_ME_OCS, and 83.3% for HMBTSC_ME_OCS). The surfactant OCS (dissolved in H2O) and the ME_OCS system showed lower efficacies, with 71.0% for OCS and 74.0% for ME_OCS system.